1990
DOI: 10.1042/bj2680387
|View full text |Cite
|
Sign up to set email alerts
|

Modulation by interferons of the expression of monocyte complement genes

Abstract: Interferons-alpha, -beta and -gamma (IFNs-alpha, -beta and -gamma) stimulated the synthesis of the second complement component (C2), Factor B (B) and C1 inhibitor (C1-inh) by human monocytes in vitro. The degree of increase of the secretion rates of C2, B and C1-inh was dose-dependent and proportional to increases in the abundances of their respective mRNAs. IFN-gamma was the most effective at stimulating monocyte C1-inh synthesis, whereas IFN-alpha and IFN-beta were marginally more effective at stimulating mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…Monocytes were cultured in the absence or the presence of dexamethasone (1 nM-1 gM) or indomethacin (0.1-10 ,M) for 24 h. Total cellular RNA was then prepared using RNAzol, and Northern blotting and double-dilution dot-blotting techniques were carried out as described previously (Lappin et al, 1990b). With the exception of blots probed with chick lysozyme cDNA, the Northern and double-dilution dot-blots were then hybridized to th-e a-32P-labelled cDNAs, washed to high stringency [0.1 x SSC containing 0.1 % (w/v) SDS at 65°C] (Lappin et al, 1990a). Blots probed with chick lysozyme cDNA were washed to a stringency of 0.5 x SSC containing 0.1 % (w/v) SDS at 65 'C.…”
Section: Mrna Abundancementioning
confidence: 99%
See 2 more Smart Citations
“…Monocytes were cultured in the absence or the presence of dexamethasone (1 nM-1 gM) or indomethacin (0.1-10 ,M) for 24 h. Total cellular RNA was then prepared using RNAzol, and Northern blotting and double-dilution dot-blotting techniques were carried out as described previously (Lappin et al, 1990b). With the exception of blots probed with chick lysozyme cDNA, the Northern and double-dilution dot-blots were then hybridized to th-e a-32P-labelled cDNAs, washed to high stringency [0.1 x SSC containing 0.1 % (w/v) SDS at 65°C] (Lappin et al, 1990a). Blots probed with chick lysozyme cDNA were washed to a stringency of 0.5 x SSC containing 0.1 % (w/v) SDS at 65 'C.…”
Section: Mrna Abundancementioning
confidence: 99%
“…Portions of nuclei (100 1l) were mixed with an equal volume of 10 mM-Tris (pH 8.3)/5 mM-MgCl2/300 mM-KCl/ 0.5 mm each of ATP, GTP and CTP/2 mM-dithiothreitol/ 100 fCi of [a-32PJUTP and incubated for 30 min at 30 'C. RNA was prepared from the nuclei using RNAzol (Lappin et al, 1990a). The [32P]RNA was dissolved in hybridization buffer (106 c.p.m./ml) and hybridization was carried out at 42 'C to cDNA immobilized on Hybond-N membranes.…”
Section: Run-on Transcription Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the cytokine regulation of complement component expression depends not only on the individual component but also on the tissue type. Cytokine regulation of C3 expression appears to be very tissue specific (3,4,7,14,16,18,(28)(29)(30)(31). Cytokine regulation of C4 expression has been less extensively studied but has been found to be upregulated in monocytes and scleral fibroblasts in response to IFN-␥ (23,25).…”
Section: Discussionmentioning
confidence: 99%
“…Up-regulation of C1-I synthesis induced by IFN-y was found in human skin fibroblasts (29), human monocytes (44,45) and human hepatoma cells (46,47). Lappin, Birnie and Whaley (48) found a stimulation of C1-I caused by each IFN-a, IFN-P and IFN-y in human monocytes in uitro. Heda et al (49) observed a twofold increase of C1-I-speciiic mRNA in human erythroleukemia cells treated with IFN-y but no alteration after incubation with IFN-a or IFN-P. Katz and Strunk (29) reported that IFN-P2 has, in contrast to IFN-y, no influence on C1-I synthesis in human skin fibroblasts.…”
Section: Discussionmentioning
confidence: 99%